USE OF PSYCHODIAGNOSTIC APPROACHES AND PRINCIPLES IN DETERMINING THE LEVEL OF SOCIO-CREATIVE COMPETENCE OF FUTURE PEDAGOGUES (Scientific journal of the Fergana State University, 2024)
In this article, the cognitive-methodical system of developing socio-creative competence in future pedagogues and the development of social activity skills and creative competence in future pedagogues in the conditions of reforms are studied. Pedagogical issues of developing socio-creative competence in future pedagogues were also analyzed based on an integrative approach.